Improving laboratory techniques to detect M. tuberculosis complex and C. neoformans as the causative agents of chronic meningitis in cerebrospinal fluid of adult patients. - Prince, Yvonne (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScMedSc (Pathology. Medical Microbiology))--University of Stellenbosch, 2010.